P1-S6.33 Monitoring chlamydia testing and positivity in the USA using data from a large commercial laboratory corporation, 2008–2010. (10th July 2011) - Hoover, K; Tao, G; Nye, M; Body, B; Kent, C
Abstract : Background: Guidelines recommend chlamydia screening of sexually active young women. Screening rates have increased over the past 10 years, but remain low. Current data used to monitor chlamydia testing trends and positivity rates have limitations, for example, national surveys provide representative data but are cross sectional and use small sample sizes, so longitudinal and subgroup analyses are not possible. To monitor trends more effectively, we solicited chlamydia testing data from commercial laboratories to obtain a representative sample of the US market. Methods: Demographic characteristics of persons tested, their geographic location, assay types, specimen sources, and test positivity by sex, age, and insurance type were assessed for all chlamydia testing performed by this laboratory corporation during June 2008–July 2010. Results: The dataset contained 3.26 million specimen records. Among those tested, 86.2% were women, 41.0% were aged 15–24 years, 73.5% had commercial insurance, 21.8% had Medicaid insurance, and 56.6% resided in the South. The most frequently used type of chlamydia test was a nucleic acid amplification test (77.5%). Among women, 59.7% of specimens were cervical, 21.1% vaginal, and 18.8% urine. Overall, 4.0% of tests were positive. Positivity rates were highest in persons aged 15–19 years, and higher in men than women for all age groups. Rates also were higher in women with Medicaid insurance than women with private insurance. Conclusions: Systematically collected laboratory data can fill a critical gap in monitoring US chlamydia testing and positivity trends. These data are more representative of the US population by geographic distribution and insurance type than other data sources. The analysis of laboratory testing data might be useful for national surveillance that would not be dependent on provider or health department reporting. Our findings underscore the importance of screening young women for chlamydia, especially adolescents in whom screening rates are low. Men had higher positivity rates probably because they sought treatment for symptoms or were referred by an infected partner. Further analysis is needed to assess if testing of persons older than 25 years was according to guidelines, such as pregnant women, at-risk persons, or symptomatic persons.